How the Fourth Statistical Account of East Lothian Recorded Developments in the Church in the County Between 1945 and 2000 - Dutton, David (Scottish church history, 2024)
This article will use the Fourth Statistical Account of East Lothian, which was produced by a consortium of local history societies, to provide a case study of how the church in the county developed between 1945 and 2000. Because East Lothian is the only Scottish county to have a fourth statistical account, the study provides a unique opportunity to trace the development of the church within a Scottish local authority during the second half of the twentieth century. The article will use, as its main sources, essays on four established denominations and the sections on ‘Belief’ in each of the parish entries. It will detail how the Church of Scotland, the Scottish Episcopal Church and the Methodist Church contracted between 1945 and 2000; show that, while the Roman Catholic Church was more stable, it began to suffer from a lack of vocations and the disinterest of younger members of the Catholic population, and that, while the Baptist Church increased its presence in the county and Pentecostal congregations and ‘house churches’ were formed, the Brethren and Church of Christ both declined and, as a consequence, these other churches remained on the margins of the church in East Lothian.